(untitled) (Research, Society and Development, 2022)
For many years, the history of early childhood education has erroneously referred to the perception that, since it is about caring for young children, the most effective thing would be for women to do it because they are more sensitive to feelings. The general objective of the research is to analyze the perception of managers, coordinators and teachers of early childhood education in relation to the male performance in this stage of teaching in the municipal network of Guaraí. In addition to identifying the possible causes related to the absence of male teachers in this area, reflecting on the paradigms that society imposes in relation to male teachers within children’s classrooms and analyzing the vision of the management team of the four municipal schools. The research has an exploratory purpose and a qualiquantitative approach, the present work was carried out in the municipality of Guaraí-TO. through the results and discussions, it was observed that the perception of managers, coordinators and teachers about the participation of male professionals in the first stage of basic education/Child Education, remains in a dogmatic position, since the institutions of early childhood education municipal do not have male professors on their staff working in the area.